Soure and Transmission Control for Wireless Visual Sensor Networks with Compressive Sensing and Energy Harvesting - Lei You; Yutong Han; Sumei Li; Xin Su (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The lifetime of the emerging Wireless visual sensor network (WVSN) is seriously dependent on the energy shored in the battery of its sensor nodes as well as the compression and resource allocation scheme. In this paper, the energy harvesting technology was adopted to provide almost perpetual operation of the WVSN and compressed-sensing-based encoding was used to decrease the power consumption of acquiring visual information at the front-end sensors. A Dynamic Source and Transmission Control Algorithm (DSTCA) was proposed to jointly determine source rate, source energy consumption, and the allocation of transmission energy and available bandwidth under energy harvesting and queue stability constraints. A virtual energy queue was introduced to control the resource allocation and the measurement rate in each time slot. The algorithm can guarantee the stability of the visual data queues in all sensors and achieve near-optimal performance. The distributed implementation of the proposed algorithm was discussed and the achievable performance theorem was also given. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2476